SOX13 dependent PAX8 expression promotes the proliferation of gastric carcinoma cells - Liang-Yu Bie; Dan Li; Yan Wei; Ning Li; Xiao-Bing Chen; Su-Xia Luo (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
PAX8 is identified as a regulator in the pathogenesis of human tumours and an indicator of the prognosis for patients. However, the role of PAX8 on proliferation in gastric cancer have not been studied. This study was aimed to explore the expression pattern of PAX8 in gastric cancer, and investigate the effect of PAX8 on the proliferation of gastric cancer cells. PAX8 and SOX13 were identified to be synchronously up-regulated in primary gastric cancer in human gastric cancer tissues and the gastric cancer datasets of TCGA, and gastric cancer patients of combined high PAX8 and SOX13 expression showed poor prognosis. Furthermore, SOX13 can mediate PAX8 and its targeted genes, Aurora B and Cyclin B1, expression in AGS and MGC803 cell lines. Flow cytometry and EdU incorporation assays showed that silencing PAX8 can block the cell cycle of gastric cancer cell in G1 phase and SOX13 expression can rescue the arrested proliferative process induced by PAX8 silenced in CCK8 and colony formation assays. Thus, combined SOX13 and PAX8 expression regulate the proliferation of gastric cancer cells, and both SOX13 and PAX8 play an oncogene function in gastric cancer.